Technological Change and the Equilibrium Level of the National Income - Ames, Edward; Ferguson, Allen R. (Quarterly Journal of Economics, 1948)
I. The problem: effects of a change in one of the Keynesian "given data, " 441. — Basic concepts: the national income in wage-units, 442; the aggregate demand function, 443; the aggregate supply function, 446; the price structure, 446. — Conditions of equilibrium, 446. — II. The meaning of technological progress, 449. — III. Effects of technological change upon the volume of the national income, 453. — Significance of the findings, 455. — IV. Employment and welfare, 455.